RESPON PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS (Zea mays Saccharata Sturt) PADA PEMBERIAN PUPUK KANDANG SAPI - Ebsan Yair Yepta Tena; I Made Suryana; I Gusti Ayu Diah Yuniti; Ni Putu Eka Pratiwi (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2023)
This study was entitled Growth Response and Yield of Sweet Corn Plants (Zea mays Saccharata Sturt) on The Application of Cow Manure. The purpose of this study is to determine the effect of cow manure on the growth and yield of sweet corn plants and to find out the effect of which cow manure provides the best growth and yield of sweet corn plants. This study used a group randomized design method (RAK) using cow manure with 6 levels, namely (K0) without cow manure, (K1) 5 tons/ha, (K2) 10 tons/ha, (K3) 15 tons/ha, (K4) 20 tons/ha, and (K5) 25 tons / ha of cow manure. The authors collected data from the parameters of plant height, number of leaves, leaf area, fresh weight of the (plant canopy, root, cob), dry weight of the (plant canopy oven, cob oven, root oven), diameter of the cob without clobot, and Length of the cob without clobot. The results have a very noticeable effect on plant height, number of leaves, leaf area, Cob length without clobot, cob diameter without clobot, fresh weight of plant canopy, fresh weight of cob without clobot, fresh weight of root, dry weight of plant canopy oven, dry weight of cob oven without clobot, and dry weight of root oven. The application of cow manure 20 ton/ha, and 25ton/ha gave the best results on the fresh weight of cobs without clots, namely 225.46 g and 230.85 g dry weight of cob ovens without clobot, namely 81,43 g and 92.07g